2015
DOI: 10.1002/ejic.201500215
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Hydroboration of a Mixed‐Donor Iminoboryl Complex of Platinum

Abstract: Keywords: Iminoboryl ligands / Platinum complexes / Boron / Main group elementsThe first iminoboryl complex with a non-phosphine donor ligand has been isolated and fully characterized. The structural and spectroscopic parameters of the Pt II complex, which bears one phosphine and one N-heterocyclic carbene ligand, suggest that the Pt center backdonates less to the iminoboryl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…X-ray diffraction studies of 4 shown in Figure b confirm its iminoborane connectivity with a nearly linear geometry of the B–B–N–B core [B1–B3–N5 angle = 176.7(8) o and B2–N5–B3 = 178.1(6) o ], demonstrating the formal sp-hybridized B3 and N5 atoms. The B3–N5 distance of 1.240(7) Å is shorter than those for structurally characterized Lewis-base-supported iminoboranes [1.300–1.360(5) Å] and comparable to the BN triple bond distances (about 1.25 Å) in typical base-free iminoborane species, which suggests considerable multiple bond character between the central boron and nitrogen atoms.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…X-ray diffraction studies of 4 shown in Figure b confirm its iminoborane connectivity with a nearly linear geometry of the B–B–N–B core [B1–B3–N5 angle = 176.7(8) o and B2–N5–B3 = 178.1(6) o ], demonstrating the formal sp-hybridized B3 and N5 atoms. The B3–N5 distance of 1.240(7) Å is shorter than those for structurally characterized Lewis-base-supported iminoboranes [1.300–1.360(5) Å] and comparable to the BN triple bond distances (about 1.25 Å) in typical base-free iminoborane species, which suggests considerable multiple bond character between the central boron and nitrogen atoms.…”
Section: Resultsmentioning
confidence: 81%
“…However, with the help of sterically bulky organyls on either side of the BN triple bond, a variety of monomeric iminoboranes IV have been isolated and structurally characterized (Chart c) . In addition, the group of Braunschweig reported the isolation of transition-metal iminoboryl complexes V , which are stable against oligomerization, yet reactive toward various substrates . In 2014, Bertrand, Stephan, and co-workers found that reactions of a cyclic (alkyl)­(amino)­carbene (CAAC) with bis­(trimethylsilyl)­dihaloboranes afford cationic iminoboryl-CAAC adducts VI .…”
Section: Introductionmentioning
confidence: 99%
“…Multimetallic transition-metal complexes containing a boron ligand have been synthesized by halide abstraction from boron, reduction of B–X bonds, and nucleophilic attack at a metal center at boron. Also, iminoboryl (BNR , ) and oxoboryl (BO , ) complexes have been synthesized and reported. Computational and experimental studies have been reported for transition-metal boryl complexes (L n M–BR 2 ). Successful experimental attempts to synthesize terminal borylene (L n M­(BR)) complexes , motivated us to model hypothetical terminal boride complexes.…”
Section: Introductionmentioning
confidence: 99%